An assessment of the effectiveness of the digital literacy program of the Quezon City Public library - Almenario, Rallion Gilbert B.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2016)
Educating people is very important in the society especially in the digital area. Nowadays, as the generation continues to embrace the world of technology, everyone should at leastknow how to use a computer or even a smart phone. Libraries can play a very good role in educating and enhancing its community especially in digital literacy. Hence, this study is centered on evaluating the Digital Literacy Program offered by Quezon City Public Library on its constituents. The program was evaluated through the users who participated during the data gathering period. A pre-test and post-test was administered to the participants to determine the capability and effectiveness of the program. The officer-in-charge of the program was interviewed for further details on program implementation.
The findings show that the program was effective in improving the digital literacy of the respondents. Scores of the respondents from the post test, both from the conceptual and practical exams, significantly improved after the modules were taught by the moderator. This signifies that the program was effective, especially that the expectations of the participants were met.
The study recommends the modification of Quezon City Public Library's module including its difficulty level. This study also recommends enhancing the promotional activities for the program to attract more participants especially during summer.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information Literacy -- Philippines -- Quezon City; Public libraries -- Information Services -- Philippines. -- Quezon City